Literature Review HR Planning: External Environment, Organizational Decisions and Employees Inventory - Ricardo Ricardo (Dinasti International Journal of Economics, Finance & Accounting, 2021)
Human resources become an essential instrument in an organization or company. To make a superior company, it is necessary to have quality human resources. Because good quality human resources will increase work effectiveness. The external environment is a factor related to HR planning, and organizational decisions are chosen as part of HR planning. In this study, researchers used descriptive qualitative methods and library research by analyzing variables related to HR planning. The purpose of the literature review research is exploratory. The results of this study are 1) Employee inventory affects HR Planning, 2) External environment affects HR Planning, and 3) Organizational decisions affect HR Planning.